2003
DOI: 10.1098/rsta.2003.1267
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation in large domains

Abstract: Pattern formation is a phenomenon that arises in a wide variety of physical, chemical and biological situations. A great deal of theoretical progress has been made in understanding the universal aspects of pattern formation in terms of amplitudes of the modes that make up the pattern. Much of the theory has sound mathematical justi¯cation, but experiments and numerical simulations over the last decade have revealed complex two-dimensional patterns that do not have a satisfactory theoretical explanation. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As the excitation amplitude increases, the physical appearance of additional capillary wave modes is known to occur. Moreover, the two-dimensional and strongly curved fluid surface permits many more capillary wave modes due to three-wave resonant interaction that is perhaps best explained by Chen and Viñals 30 and Rucklidge 31 who showed the formation of patterns similar to capillary waves appearing on temporal scales remarkably different than that of the excitation signal. Moreover, the two-dimensional and strongly curved fluid surface permits many more capillary wave modes due to three-wave resonant interaction that is perhaps best explained by Chen and Viñals 30 and Rucklidge 31 who showed the formation of patterns similar to capillary waves appearing on temporal scales remarkably different than that of the excitation signal.…”
Section: Introductionmentioning
confidence: 98%
“…As the excitation amplitude increases, the physical appearance of additional capillary wave modes is known to occur. Moreover, the two-dimensional and strongly curved fluid surface permits many more capillary wave modes due to three-wave resonant interaction that is perhaps best explained by Chen and Viñals 30 and Rucklidge 31 who showed the formation of patterns similar to capillary waves appearing on temporal scales remarkably different than that of the excitation signal. Moreover, the two-dimensional and strongly curved fluid surface permits many more capillary wave modes due to three-wave resonant interaction that is perhaps best explained by Chen and Viñals 30 and Rucklidge 31 who showed the formation of patterns similar to capillary waves appearing on temporal scales remarkably different than that of the excitation signal.…”
Section: Introductionmentioning
confidence: 98%
“…We suggest that the hard squares represent a superlattice structure where several wave vectors interact to suppress the ZZ instability. Such superlattices, which often represent quasiperiodic structures, have been of considerable interest recently [26,27]. They have been investigated experimentally, in particular, in the Faraday instability in cells with aspect ratio below about 50 [28].…”
mentioning
confidence: 99%
“…Rhombic patterns were found to appear to be natural at the primary instability in the form of a bicritical point. Under two-frequency parametric excitation, Rucklidge [342] considered pattern formation in large domains with an attention to QPs, where the appearance of small divisors causes the standard theoretical method to fail. The symmetry-based approach developed by Tse et al [343] was used by Rucklidge et al [344] to analyze three observed spatial period-multiplying transitions from an initial hexagonal pattern.…”
Section: Two-frequency Parametric Excitation It Is Believed That Edwmentioning
confidence: 99%